Beware of Analogies - Hönigová, Alena; Mestek, Jaroslav (Teorie vědy / Theory of Science, 2013)
This book review study observes the analogy, which has formed a basis for Douglas R. Hofstadter's method of research and writing in the book Gödel, Escher, Bach (Prague: Argo - Dokořán 2012, 830 p.). As opposed to Hofstadter's concept of analogy, besides other issues illustrated by misleading examples of J. S. Bach's composition work, the analogy in this study is given a more precise exactitude. At the same time the insufficiencies of musical examples, which would probably not be revealed by readers without direct linkage to the musical theory, are being corrected in this study. These aspects are followed in this study towards the conclusion, that the influential book under this review, wrong fully aspiring to the universal methodology, belongs to the general non-fiction literature.